1961
DOI: 10.1083/jcb.9.1.193
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Fibrils From Collagen Solutions

Abstract: The kinetics of collagen reprecipitation from solutions of salt-extracted calf dermis in the presence of small amounts of mucopolysaccharidc and nucleic acids (0.005 per cent in the final reaction mixture) has been reported by . The present paper is a parallel study using the same materials, and describes the electron microscopic (EM) morphology of the collagen precipitates replicated after 24 hours at room temperature. Satisfactory, uncontaminated EM preparations were obtained which showed that all the deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1964
1964
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…Consistent with previous findings, CRM micrographs suggested that cold cast collagen hydrogels contained larger fibers relative to warm cast hydrogels (Fig. 2a) [27], [28], and [29]. Interestingly, the addition of Matrigel appeared to increase fiber size in cold cast collagen hydrogels, while appearing to have no effect under warm cast conditions.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with previous findings, CRM micrographs suggested that cold cast collagen hydrogels contained larger fibers relative to warm cast hydrogels (Fig. 2a) [27], [28], and [29]. Interestingly, the addition of Matrigel appeared to increase fiber size in cold cast collagen hydrogels, while appearing to have no effect under warm cast conditions.…”
Section: Resultssupporting
confidence: 89%
“…Although the biochemistry of fibril assembly was largely established 50 years ago, [16,17] many details of how 3D collagen fibril networks assemble, grow and adapt remain elusive. Fibrillogenesis is driven by the formation of short-range non-covalent, ionic, hydrogen and hydrophobic bonds between molecules lying in quarter-stagger register.…”
Section: Discussionmentioning
confidence: 99%
“…assembly [17] but are limited in explaining the dynamic (remodelling) of matrices. [18] It is assumed here that at least some degree of this cyclical load-dependent fusion process will occur in any new tissue in vivo under load, just as in vitro fibrillogenesis is a simple model of the in vivo process, however the extent of this and its local importance is yet to be tested.…”
Section: Full Papermentioning
confidence: 99%
“…As suggested by McKusick (18), however, in dominant diseases (such as DDEB), an alteration in the synthesis of a critical structural macromolecule might well be expected to be expressed as an abnormal phenotype. In this regard, there is considerable evidence to indicate that glycosaminoglycans interact with collagen to influence both the rate and quality of collagen fibril formation (19). Indeed, whereas some mucopolysaccharides promote fibril formation (20,21), others hinder it (22).…”
Section: Discussionmentioning
confidence: 99%